IMPLEMENTASI MODEL PEMBELAJARAN PASPOR (PAIRING, SQUARE, PRESENTATION, REPETITION) UNTUK MENINGKATKAN KETERAMPILAN KOLABORATIF SISWA KELAS X TKJ SMK NEGERI 1 RAMBAH - Nindi Bunga Iqnas Bunga; Jufri Jufri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the effect of the PASPOR learning model (Pairing, Square, Presentation, Repetition) on students' collaborative skills. This research uses a quantitative approach with a quasi-experimental design, specifically the nonequivalent control group design. The population of this study was all students of class X TKJ at SMK Negeri 1 Rambah, with two classes selected as samples, namely the experimental class and the control class. Data were collected through observation, questionnaires, and pretest-posttest. Data analysis techniques included normality test (Shapiro-Wilk), Mann–Whitney test, N-Gain, and effect size. The results showed that the application of the PASPOR model had a significant effect on improving students' collaborative skills. The N-Gain results indicated a moderate improvement, and the effect size showed a strong influence. Thus, the PASPOR model is effective in enhancing collaborative skills in vocational high school students.